2012
DOI: 10.1143/jjap.51.06fb11
|View full text |Cite
|
Sign up to set email alerts
|

Study on Image Drift Induced by Charging during Observation by Scanning Electron Microscope

Abstract: The mechanism of image drift in the observation of a boundary between a metal and an insulator by scanning electron microscope (SEM) is clarified by electron-trajectory simulation and experiment. In the region involving a straight boundary between a large-area metal layer and an insulating substrate, the largest image drift is expected to be observed owing to an asymmetric charging on the sample surface. The simulation result shows that a metal–insulator boundary in the SEM image shifts toward the metal part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This could be due to imperfections in the used mask (i.e., a replica of a mask made by electron beam lithography) which were transferred directly into the PR patterns. Additionally, the loss of focus and drifting of the HR‐SEM images during a slow scan speed could also add to some inaccuracy during image processing and analysis by using ImageJ software. Overall these images indicate a robust fabrication process.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to imperfections in the used mask (i.e., a replica of a mask made by electron beam lithography) which were transferred directly into the PR patterns. Additionally, the loss of focus and drifting of the HR‐SEM images during a slow scan speed could also add to some inaccuracy during image processing and analysis by using ImageJ software. Overall these images indicate a robust fabrication process.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the direction of the image drift coincides with the scan‐direction of the electron beam. This is in contrast to previous assumptions stating independence of the two (Okai & Sohda, ). The image drift can in fact be completely eliminated for any image/structure by carefully aligning the objective aperture and the stigmation of the beam, resulting in a still image similar to that of a conductive sample.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of insulating materials is a well‐known challenge in SEM (Cazaux, ; Joy & Joy, ; Thong et al ., ; Ose et al ., ; Goldstein et al ., ; Okai et al ., ; Okai & Sohda, ). Insulating samples do not provide a path to ground and therefore accumulate charge.…”
Section: Introductionmentioning
confidence: 97%
“…Electron beam-based inspection techniques have become a standard where nanometer resolution imaging is required for state of the art semiconductor devices. However, when non-conductive materials are involved, charging occurs and issues are reported such as image distortions due to the primary beam deflections [1]- [5] and image contrast changes due to the changing secondary electron (SE) emission [6], [7, p. 127], [8]. As a consequence measurements of critical dimensions (CD) will be less accurate [9]- [11].…”
Section: Introductionmentioning
confidence: 99%